The Effect Of Using Cooperative Script Model On Students' Reading Comprehension Of Descriptive Texts At SMA Negeri 6 Padangsidimpuan - Siregar, Nita Syafitri; Meidipa, Lisa Fitri; Ramadhani, Yulia Rizki (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2025)
This research investigates the effectiveness of the Cooperative Script Model in improving students' reading comprehension of descriptive texts at SMA Negeri 6 Padangsidimpuan. The study employs a quasi-experimental design with a nonequivalent control group, involving 60 tenth-grade students divided equally between experimental and control groups. Data collection utilized pre-tests and post-tests consisting of 25 multiple-choice questions measuring various reading comprehension skills. The experimental group received instruction through the Cooperative Script Model, while the control group was taught using conventional methods. Statistical analysis revealed that students taught using the Cooperative Script Model achieved significantly higher scores (mean=77.50) compared to those taught conventionally (mean=69.50). The t-test results (t=8.782, p<0.05) confirmed a significant difference in reading comprehension between the two groups. These findings demonstrate that the Cooperative Script Model effectively enhances students' descriptive text comprehension by fostering collaborative learning, active engagement, and mutual teaching opportunities. The study contributes to the growing body of evidence supporting cooperative learning approaches in English language education.